Do Professional Norms in the Banking Industry Favor Risk-taking? - Cohn, Alain; Fehr, Ernst; Maréchal, Michel André (Review of Financial Studies, 2017)
In recent years, the banking industry has witnessed several cases of excessive risk-taking that frequently have been attributed to problematic professional norms. We conduct experiments with employees from several banks in which we manipulate the saliency of their professional identity and subsequently measure their risk aversion in a real stakes investment task. If bank employees are exposed to professional norms that favor risk-taking, they should become more willing to take risks when their professional identity is salient. We find, however, that subjects take significantly less risk, challenging the view that the professional norms generally increase bank employees’willingness to take risks.